Impression Management Komunitas Role player K-POP dalam Media Sosial Twitter - Rienadhy, Anindya Cindy Dama (Tuturlogi: Journal of Southeast Asian Communication, 2022)
The emergence of K-Pop in Indonesia has given rise to a rapidly evolving fan culture on various social media platforms, one of which is Twitter. Fandom communities on Twitter have, in turn, brought forth a new phenomenon: the emergence of K-Pop Roleplayer communities. K-Pop Roleplaying involves participants assuming the personas of Korean celebrities as characters in their interactions. Since players essentially 'borrow' the identities of others in this game, terms like "In Character" (IC) and "Out of Character" (OOC) have arisen, which can be explored through the same concepts found in impression management, namely the "front stage" and "back stage." This qualitative research, employing a netnographic approach, seeks to understand how K-Pop Roleplayers engage in impression management in their daily activities and how effectively they can portray the chosen celebrity characters. The study also examines the real-life impacts of Roleplay on the participants. The research was conducted using netnography methods, including observation and semi-structured interviews with five informants who are K-Pop Roleplayers.The findings of this study are as follows: K-Pop Roleplayers consider their Twitter timelines as their "front stage." The objective of their impression management is to create a positive image of the characters they portray. They achieve this through the appearance of their accounts and the content they post. The "back stage" in this context is considered to be their online accounts, and Roleplaying has a noticeable influence on the real lives of the participants. This research makes a valuable contribution to the field of communication studies, especially in the realm of social media dramaturgy.